Iklan Televisi dan Perilaku Konsumtif Anak-Anak (Studi Kasus Pada Siswa SDN 13 Serang) - Neka Fitriyah (Universitas Al Azhar Indonesia, 2015)
The aim of this research was to comprehend the influence of TV commercials toward the children consumptive behavior. To attain that purpose, an analytical survey method was adopted. The sample was using the cluster random sampling technique of 13th Primary School of Serang. Based on the minimal amount and the Krejcie table, 39 student were taken as its sample. The primary data were obtained by questionnaire, interview and observation then those were enriched by documentation analysis as the secondary data. The data collected were slogan, commercial model, repetition, and motivation. Those were analyzed by path analysis. The result showed that aside of the following factors : slogan, model, repetition, motivation, were partially significant in influencing the childrens attitude to the product. Slogan, model, repetition, motivation, age, education and attitude were collectively significant in influencing consumptive behaviour of the childrens. Partially the age and social community had no significant influence